Peak Loads and Efficient Pricing: Further Comment - Houthakker, H. S. (Quarterly Journal of Economics, 1958)
Peak Loads and Efficient Pricing: Further Comment Get access H. S. Houthakker H. S. Houthakker Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 72, Issue 3, August 1958, Pages 463–464, https://doi.org/10.2307/1882235 Published: 01 August 1958